2006
DOI: 10.1128/jvi.80.2.999-1014.2006
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Patterns of Change during the Divergence of Human Immunodeficiency Virus Type 1 Envelope from That of the Inoculated Virus in Simian/Human Immunodeficiency Virus-Infected Macaques

Abstract: We have analyzed changes to proviral Env gp120 sequences and the development of neutralizing antibodies (NAbs) during 1 year of simian/human immunodeficiency virus SHIV-89.6P infection in 11 Macaca nemestrina macaques. Seven macaques had significant env divergence from that of the inoculum, and macaques with greater divergence had higher titers of homologous NAbs. Substitutions in sequons encoding potential Nlinked glycosylation sites (PNGs) were among the first to be established, although overall the total nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 67 publications
7
64
1
Order By: Relevance
“…The accumulation of mutations was especially noticeable at late time points (22 March 2006 [3/22/06] and thereafter). In addition, over time, changes in potential N-glycosylation sites (PNGS) accumulated in previously identified hot spots (V1, V2, V4, and V5) (59,60) and in the C2 region of Env and in gp41 as neutralization breadth increased (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of mutations was especially noticeable at late time points (22 March 2006 [3/22/06] and thereafter). In addition, over time, changes in potential N-glycosylation sites (PNGS) accumulated in previously identified hot spots (V1, V2, V4, and V5) (59,60) and in the C2 region of Env and in gp41 as neutralization breadth increased (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations that resulted in the loss of PNLG sites included sites that have been demonstrated to be conserved or selected in a long-term infection in a simian/human immunodeficiency virus model (N339 and N386) (10). Other PNLG sites that were lost have been identified as central in a network of coevolving PNLG sites (N411) (74).…”
Section: Discussionmentioning
confidence: 99%
“…Escape from autologous NAbs (41,58) is due to alterations to Env characterized by entropic masking (27), flexibility in size and the positioning of the variable loops (10,16), amino acid sequence variation (25), and glycosylation changes (8,58). Indeed, during the course of infection, the location of potential N-glycosylation sites (PNG) is altered (3) and the number of PNGs is increased (44). Recent studies (36,43) demonstrated that multiple pathways are involved in escape from autologous NAbs in clade C-infected patients and the pathways are context dependent, as they vary from patient to patient and during the course of infection.…”
Section: A Major Goal Of Human Immunodeficiency Virus Type 1 (Hiv-1) mentioning
confidence: 99%